2006
DOI: 10.1093/toxsci/kfl114
|View full text |Cite
|
Sign up to set email alerts
|

Nonylphenol and Octylphenol-Induced Apoptosis in Human Embryonic Stem Cells Is Related to Fas-Fas Ligand Pathway

Abstract: Human embryonic stem (hES) cells have been proposed as a source of various cell types for cell replacement therapy. Besides their potential in therapeutic uses, ES cells also have other potential applications, such as in drug discovery and in vitro screening assays of various toxicants. Nonylphenol (NP) and octylphenol (OP) are common environmental contaminants, known to disrupt the reproductive and endocrine system. However, little is known about their toxicological effects on early embryonic development in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 42 publications
6
29
0
Order By: Relevance
“…Accumulating studies have revealed that NP toxicity induces oxidative stress through the generation of ROS and stimulates apoptosis in a variety of cell types, including human embryonic stem cells, TM4 SCs and testicular SCs (Choi et al 2014;Gong et al 2009;Kim et al 2006;Kuo et al 2012;Zhang et al 2014). NP activates endoplasmic reticulum stress response, Fas/FasL, MAPKs, Akt and JNK signaling pathways, resulting in changes in cell survival, cell cycle progression and apoptosis (Choi et al 2014;Duan et al 2016c;Lepretti et al 2015;Liu et al 2015;Yao et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have revealed that NP toxicity induces oxidative stress through the generation of ROS and stimulates apoptosis in a variety of cell types, including human embryonic stem cells, TM4 SCs and testicular SCs (Choi et al 2014;Gong et al 2009;Kim et al 2006;Kuo et al 2012;Zhang et al 2014). NP activates endoplasmic reticulum stress response, Fas/FasL, MAPKs, Akt and JNK signaling pathways, resulting in changes in cell survival, cell cycle progression and apoptosis (Choi et al 2014;Duan et al 2016c;Lepretti et al 2015;Liu et al 2015;Yao et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…hESC were used recently to evaluate the ability of nonylphenol and octophenyl, two environmental contaminates that disrupt the reproductive and endocrine systems, to induce apoptosis [47]. Using a variety of methods, this study found that these test chemicals did induce apoptosis in hESC via a Fas-Fas ligand pathway in which caspase 8 and 3 activation increased following exposure to the test chemicals.…”
Section: Examples Of Studies That Have Been Donementioning
confidence: 93%
“…It has also been postulated that hES cells could be used for reproductive toxicity screening in vitro (Krtolica & Giritharan 2010) as well as for drug discovery to minimize unexpected toxicity when entering a clinical trial (Jensen et al 2009). Using undifferentiated hES cells in an in vitro screening assay, Kim et al (2006) reported that exposure to the organic compounds such as nonylphenol (NP) and octylphenol (OP) decreased expression of Oct4 and Nanog in a dose-dependent manner. As Oct4 and Nanog are transcription factors required for maintaining stem cell pluripotency and self-renewal, it is likely that NP and OP decrease hES pluripotency.…”
Section: Susceptibility Of Embryonic Stem Cells To Edc Exposurementioning
confidence: 99%
“…As Oct4 and Nanog are transcription factors required for maintaining stem cell pluripotency and self-renewal, it is likely that NP and OP decrease hES pluripotency. Furthermore, NP and OP were cytotoxic, inducing DNA fragmentation and hES cell death through Fas-Fas ligand interactions and caspase-3 and -8 activity (Kim et al 2006). Interestingly, hES cellderived neural progenitor cells showed greater sensitivity to NP and OP exposure, possibly through the downregulation of ATP-binding cassette transporters known to pump out toxicants (Kim et al 2006).…”
Section: Susceptibility Of Embryonic Stem Cells To Edc Exposurementioning
confidence: 99%